Format Siaran Dakwah Radio Arrisalah 95,7 FM Dalam Memotivasi Membaca Al-Qur’an di Kalangan Ibu-Ibu di Kecamatan Tanjung Morawa Kabupaten Deli Serdang - Anggun Dwi Nanda NST; Erwan Efendi (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
A radio station with the name Radio Arrisalah 95.7 FM stands with its own special features from other stations, namely with its Islamic character. One of the most riveting programs that has been able to attract loyal listeners over the years is the Tahsin program. As a result, this program has become a learning tool for all ages, especially mothers who regularly listen to the Tahsin program on Arrisalah Radio 95.7 fm to listen to it every day. The purpose of this study was to find out whether using the da'wah broadcast style on Arrisalah radio can improve mothers' understanding of reading the Koran. Descriptive qualitative approach is used in this research. In order to understand the characteristics of the content, the research data was collected through scientific research methods, observation and interviews. The findings of this study indicate that reading the Qur'an has increased understanding further than before. Keywords : Dakwah Broadcast Format, Arrisalah Radio 95.7 Fm, Motivates Reading Al-Qur'an Among Mothers.